Irish Jesus, Roman Jesus : the formation of early Irish Christianity - Snyder, Graydon F. (Trinity Press International, 2002)
Nearly two thousand years before the Roman Empire, a group of Celts wandered into the Mediterranean basin, establishing a home in the region of Galatia, modern-day Turkey. They brought with them their political and economic systems, their cultural practices, and their religious traditions. Paul of Tarsus visited Galatia and established churches there. But after his visit, troubling news reached him. Despite Paul's teaching, the Galatian churches were arguing over the correct practice of the Jesus tradition. Paul made a second visit, followed by his letter to the Galatians. In his Irish Jesus, Roman Jesus, Graydon Snyder looks to Galatia for the origins of Irish Christianity, and points to the possibility of a very different course for Christian history. He shows how the religious practices and beliefs of the Galatians--more properly called the Celts--did not fit Paul's teaching and interpretation of the Jesus tradition. The Celts eventually moved to Ireland. The Christianity that they developed there, promulgated by Patrick and others, sharply contrasted with Paul's version that is at the roots of Western orthodox Christianity. If the Celts rather than the Romans had won the day, contemporary Christianity would look very different indeed.